Pupils' participation roles in school-based physical activity in the context of physically active learning and recess: experiences from Norwegian and Estonian primary and secondary school pupils - Pardali, Eirini; Kjønniksen, Lise; Bratland-Sanda, Solfrid; Säre, Egle; Koni, Ingrid; Lemberg, Getter Marie; Mäestu, Evelin; Kull, Merike; Mandelid, Mathias Brekke; Trangsrud, Lise Katrine Jepsen (Frontiers in Sports and Active Living, 2025)
IntroductionThe role of pupil participation in school-based physical activity is an often overlooked element despite the increasing interest in pupils' voices in policy development and research. Pupil participation is here defined as collaborative actions involving pupils and school stakeholders that influence decision-making processes in school-based physical activity. This study was conducted to explore how the 10- and 15-year-old pupils perceive their participation roles in school-based physical activity connected to age and the contexts of physically active learning and recess in various schools in Norway and Estonia.MethodsThe study involved thirty-eight students (n = 38; 17 boys and 21 girls; 21 10-year-olds and 17 15-year-olds) from selected schools in Norway and Estonia. Data were gathered through nine semi-structured focus group discussions.ResultsUtilizing Braun and Clarke's reflexive thematic analysis, three principal themes were constructed: 1. The informed and listened to, 2. The responsible and open to teachers' questions and facilitation, and 3. The invited to make a choice and practice participation. Taken together, the themes reflected the existing practices and structures that empowered pupils to express their perspectives on school-based physical activity. They also encapsulated pupils' suggestions and wishes for facilitation of their voices in these activities.DiscussionUsing Hart's Ladder of Children's Participation as a theoretical lens, the study revealed age and context-specific disparities in pupils' participation roles in school-based physical activity. Pupils engaged in both informal and formal participation structures in teacher-led physically active learning and free choice recess activities, creating democratic spaces for rights of participation and the expression of choice, which need to be prioritized. Older pupils had more participation opportunities than 10-year-olds and had more responsibility, possibly due to perceived maturity. However, 10-year-olds exhibited numerous ideas for increased movement in school, valued the pupils' council, and called for more physical activity. Activity choice and teacher facilitation are vital in physically active learning and recess contexts. It is suggested that school-based physical activity can offer a space for pupils to learn about democracy but gaining the confidence and ability to do so takes practice. Meanwhile, teachers often need training to support active pupil participation in school-based physical activity.